Food consumption, type 2 diabetes mellitus and weight status among adults in the Lingwala Health Zone, Kinshasa, the Democratic Republic of the Congo - Marthe Sikayako Kikwayabo; Théophane Kekemb Bukele; Bavon Mupenda (Journal of Global Health Economics and Policy)
# Background